The Homeland of Stereotypes - Hossein Keramatfar (k@ta: A Biannual Publication on the Study of Languange and Literature, 2018)
Following the trenchant critique of orientalism, orientalist discourse has employed complex strategies to create ambivalent non- Western stereotypes. The earlier fixed oriental characters are often discarded; they are instead accorded certain amounts of flexibility. However, the fact is that despite such changes and these less negative images, orientalist discourse continues producing the Oriental other to perpetuate Western domination. In fact, it simply draws upon old repertoire of stereotypes, recycles them, and produces new ones; only care is taken that they do not sound as markedly negative as the old ones. The present paper seeks to investigate how the American TV series Homeland (2011-) repeats the imperialist claims of the orientalist discourse by presenting a range of oriental character types, from the classic Muslim terrorist to some less negative characters. It employs â€œNegative formulasâ€ to produce more ambivalent stereotypes to reinforce the alleged essential superiority of America. The series stages the character of the captive mind as the ideal oriental type to be imitated by all Orientals. The paper also demonstrates that how Homeland employs the orientalist theme of nativization, again only to prove the eventual un-contaminability and superiority of the West. Islam and Iran are the particular targets of Homelandâ€™s stereotyping.